The sum of cubes (of two numbers) formula is represented as a3 + b3. Without having to calculate the cubes, the a cube plus b cube formula is used to obtain the sum of the two cubes. It is also employed in the factorization of cube binomials. In this section, we’ll go through the many aspects of the a3 + b3 formula.

The sum of cubes of the two numbers is also known as the formula of a cube plus b cube. This algebraic formula can be used to compute the sum of cubes of two numbers. A binomial is a cube + b cube (a3 + b3) that can be factored using the formula.

You may evaluate the a3 + b3 formula by multiplying (a + b) (a2 – ab + b2) and seeing if you obtain a3 + b3. The a3 + b3 formula, sometimes known as the difference of cubes formula, is as follows:

a3 + b3 = (a + b) (a2 – ab + b2)

**Proof of a3 + b3 Formula**

Let us see the proof of a cube plus b cube a3 + b3 formula below.

- To prove that a3 + b3 = (a + b) (a2 – ab + b2)

we need to prove here LHS = RHS. Let’s begin with the following steps.

LHS = a3 + b3

On Solving RHS side we get,

= (a + b) (a2 – ab + b2)

On multiplying the a and b separately with (a2 – ab + b2) we get

= a (a2 – ab + b2) + b(a2 – ab + b2)

= a3 – a2b + ab2 + a2b – ab2 + b3

= a3 – a2b + a2b + ab2– ab2 + b3

= a3 – 0 + 0 + b3

= a3 + b3

Hence proved, LHS = RHS

Now Let us see the proof of a cube plus b cube a3 + b3 formula below.

To prove that (a + b)3 = (a3 + b3 )- 3ab(a + b)

we need to prove here LHS = RHS. Let’s begin with the below steps.

(a + b)3 = (a3 + b3 )- 3ab(a + b)

Now, Subtract the 3ab (a + b) from each side of the above Equation.

(a + b)3 – 3ab(a + b) = a3 + b3

Therefore, the formula for (a3 + b3) is

(a3 + b3)= (a + b)3 – 3ab(a + b)

(a3 + b3)= (a + b)[(a + b)2 – 3ab]

(a3 + b3)= (a + b)[a2 + 2ab + b2 – 3ab]

(a3 + b3)= (a + b)(a2 – ab + b2)

Therefore, the formula for (a3 + b3) is

(a3 + b3)= (a + b)(a2 – ab + b2)

So,

(a + b) and (a2 – ab + b2)

are the factors of (a3 + b3)

Thus, (a + b)3 = (a3 + b3 )- 3ab(a + b)

**How to Use a3+b3 Formula?**

The following steps can be taken while using a3 + b3 formula.

- Firstly, observe the pattern of the 2 numbers and check the numbers have 3 as power or not.
- After that, note down the formula of and that is a3 + b3 = ( a + b) ( a 2 – a b + b2)
- Now, Substitute the values of the a and the b in a3 + b3 formula.
- Lastly, multiply a and b one by one with (a2 – ab + b2) and simplify to get the result.

**Point To remember**

- (a + b)3 = (a3 + b3 )- 3ab(a + b)
- a3 + b3 = (a + b) (a2 – ab + b2)